Optimizing the Role of State Administrative Court Decisions in State Financial Recovery - Yulius, Yulius; Utama, Yos Johan (LAW REFORM, 2024)
The government has significant authority in managing state finances, demonstrated by its ability to enact laws and to take public legal action through government decisions and actions. A number of authorities are inextricably linked to the measures taken to ensure that state finance can fund all state expenditures related to achieving development goals. This considerable power may violate citizens' rights due to the decisions or actions of the state finance manager. The community whose rights are jeopardized may file a lawsuit or petition the Administrative Court. The Administrative Court Decision must be able to synthesize public demands with the stability of the state finance to ensure that justice and legal order are fulfilled for the benefit of the state and people. This research is a normative legal research with statutory and conceptual approaches. This research concludes that the Administrative Court decision has enforced the law and harmonized and actualized the national legal system regarding state finances. It is also highly correlated with state financial stability because its value is immense and can affect the state's cash balance.